The effect of the 2-week wait referral system on the detection of and mortality from colorectal cancer: protocol of a systematic review and meta-analysis. Issue 1 (December 2016) - Mozdiak, Ella; Tsertsvadze, Alexander; McFarlane, Michael; Widlak, Monika; Tabuso, Maria; Dunlop, Amber; Arasaradnam, Ramesh
Abstract Background Colorectal cancer represents the fourth most common cancer in England and Wales; survival is high for early stage disease but declines sharply with advanced stage. UK figures suggest that cancer survival rates are lower than those of other Western European countries. Current 5-year survival is around 50 %. A rapid access strategy was introduced through the Department of Health in 2000. This 2-week wait (TWW) referral pathway was devised to streamline referral for suspected cancer, allow diagnosis at an earlier stage, reduce cancer survival inequality and reduce cancer-related mortality. However, only around half of patients with colorectal cancer have symptoms that fit the TWW criteria plus there is a fourfold difference in referral rates across England and Wales. High-quality evidence of TWW outcome measures for colorectal cancer is lacking. This systematic review will collate and evaluate the latest evidence on colorectal cancer detection rate, stage at diagnosis and mortality. Methods English-language publications from 2000 reporting outcomes on the TWW referral system for suspected colorectal cancer will be eligible for inclusion. Cochrane, EMBASE, MEDLINE via PubMed, NHS Evidence, Trip and the British Library Catalogue databases will be searched. Two paired reviewers will independently screen all titles/abstracts and full text for eligibility, then extract data and assess for bias using standardised formats. They will hand review reference lists of eligible articles. Disagreement will be resolved via third party adjudication. Summary effect measures for post-referral diagnosis and mortality rates will be calculated and expressed as relative risk, hazard rate ratio or risk difference with corresponding 95 % confidence intervals. Where possible summary effect measures will be pooled, heterogeneity and its extent for pooled estimates will be assessed via visual inspection of forest plots and explored via sub-group analysis. Discussion In this systematic review, we aim to summarise the relevant evidence on cancer detection rate, cancer stage at diagnosis and disease-related mortality rates for patients with suspected colorectal cancer investigated through the TWW referral system in England and Wales. We will highlight gaps in the evidence and provide a better understanding of whether it is meeting its desired effect. Systematic review registration PROSPEROCRD42016037368